Community informed recommendations for a campaign to promote awareness of long-acting injectable PrEP among Latino men who have sex with men - Ronald A. Brooks; Omar Nieto; Martin Santillan; Elena P. Rosenberg-Carlson; Jose R. Segura-Bermudez; Dilara K. Üsküp (PLoS ONE, 2026)
Background Across the United Sates, Latino men who have sex with men (LMSM) face disproportionately high HIV risk. Although pre-exposure prophylaxis (PrEP) effectively reduces HIV risk, numerous barriers limit PrEP access among LMSM. Culturally tailored public health campaigns provide one potential strategy for increasing access, awareness, and use of PrEP, including the newest long-acting injectable PrEP (LAI PrEP) formulations. The purpose of the study was to develop community-informed recommendations for a culturally responsive LAI PrEP awareness campaign designed for LMSM. Methods Between June 2023 to March 2024, thirty LMSM participated in four virtual focus groups conducted in Los Angeles, CA. LMSM were recruited through a larger LMSM-centered HIV prevention intervention. In the focus groups, participants shared their perspectives on campaign messaging, imagery, tone, and accessibility. Coding reliability thematic analysis was used to analyze the data. Results Findings suggest that a LAI PrEP campaign for LMSM should: provide basic information about the strategy; highlight its benefits; incorporate humorous and sex-positive messaging or imagery; communicate the seriousness of HIV without stigmatizing, blaming, or scaring LMSM; incorporate important Latine cultural values; and include Latine celebrities, public figures, and everyday individuals as messengers. In addition, there were mixed opinions regarding the use of a syringe in the imagery, with some participants advocating against its use to avoid fear- and pain-based associations with injections. Finally, participants believed that a LAI PrEP campaign should be made accessible to LMSM by providing materials in both English and Spanish and placing physical advertisements in neighborhoods predominately occupied by Latine people. Conclusions Our findings offer several practical recommendations for developing a LAI PrEP awareness campaign for LMSM that can be used by health departments, community-based organizations, and others. Incorporating community insights is crucial to ensure that a campaign resonates with and meets the needs of the LMSM community.